TINGKAT KEBERHASILAN INSEMINASI BUATAN PADA BABI MENGGUNAKAN SEMEN YANG DIBERI EKSTRAK MESOCARP Borassus ?abellifer Linn YANG DI PRESERVASI SELAMA 4 HARI PADA SUHU13°C - Hermilinda Parera; Bernadus Ndoen; Yonas Lino; Nathan Adoe (Partner, 2018)
This study aims to determine the succesfull of artificial insemination (AI) in sows using semen added with 0,01% mesocarp extract of Borassus ?abellifer Linn as an antioxidant source and preserved at 13 °C for four days. This study used 16 Duroc-Landrace crossbred sows with ages of 1-3 years that had given birth for at least 1 time. The sows was divided into two groups: group I (K1) using semen with Beltsville Thawing Solution (BTS) diluent preserved at 13 °C for 3 days, and Group II (K2) usingsemen with BTS diluent given 0.01% extract mesocarp B. flabellifer Linn and preserved at 13 ° C for four days. Evaluation of the success rate of artificial insemination were described by the number of non retrun rate (NRR), service per conception (S/C) and conception rate (CR), which continued analyzed using t-test. The results showed that the NRR value of the K1 and K2 were not significantly different (P> 0.05) between the two groups with values of 80% and 77,7%, respectively. The S/C value of group K1 was 1.25 was not significantly different (P> 0.05) from the K2 with the value of 1.125. Whereas, the value of CR of the K1 is 75% showed no significant difference with the K2 87.5% (P> 0.05). It can be concluded that the use of semen given BTS diluent and 0.01% mesocarp extract B.flabellifer Linn and preserved at 13 ° C for up to 4 days can be used in artificial insemination, because it has the same capabilities with semen that given BTS diluent and preserved at 13 ° C for 3 days.